Milícia e «Santidade» no agiologio lusitano dos santos, e varoens ilustres em virtude do reino de portugal, e suas conquistas(1652,1657,1666,1744) de Jorge Cardoso e D. António Caetano de Sousa - Paula Almeida Mendes (Universidade do Porto, 2013)
Based on the examples of military «saints» included in the four volumes of Agiologio Lusitano dos Santos, e Varoens ilustres em virtude do Reino de Portugal, e suas conquistas (published between 1652 and 1744), by Jorge Cardoso and D. António Caetano de Sousa, this article seeks to draw attention to the sustainability of the prestige that accompanies this hagiographic model and the various updates that it suffered, in a context marked by the attempt to construct a history of the territorial «sanctity» of portuguese kingdom, enabling it to rival with other European catholic spaces.